Effect of financial ratios on the stock price: A case study of plantation sector In Malaysia - Mohd Rustam Usman; Ilmas Abdurofi (Universitas Gadjah Mada, 2025)
The plantation sector is a key sector in the Malaysian economy, with a significant contribution to the nation's GDP. This study examines the relationship between financial ratios and stock prices of the plantation industry in Malaysia. The study adopts a quantitative research design to examine the effect of individual and combination of financial ratio on stock prices of 30 plantation companies at Kuala Lumpur Stock Exchange (KLSE). The predetermined and random effect models are presented to estimate the panel data model and Hausman specification test applied to define appropriate model for either the fixed or random effects. The results reveal that the majority of individual financial ratio can predict future capital gain on agribusiness stocks, while the ratio of book to market value (BM) contributes as a highest predictive power on capital gain. The correlations identified between these financial metrics and stock returns underscore the importance of financial analysis in investment decision-making, highlighting how nuanced assessments of a company's financial statements can reveal significant opportunities for informed investment strategies. Furthermore, the study accentuates the necessity for robust financial reporting standards and practices that can enhance the accuracy of financial reporting, thereby contributing to a more transparent and reliable market ecosystem.